On the modelling of vibrations of functionally graded plates - Kaźmierczak-Sobińska, Magda; Jędrysiak, Jarosław (Wydawnictwo Politechniki Łódzkiej, 2012)
In this paper there are considered functionally graded plates. To describe vibrations of these plates and take into account the effect of the microstructure it is applied the tolerance method, cf. [10, 11]. There are formulated governing equations of three presented models: the tolerance model, the asymptotic model and the combined asymptotic-tolerance model.

W pracy rozpatrywane są płyty o funkcyjnej gradacji własności. Aby opisać drgania tych płyt, wykorzystano technikę tolerancyjnego modelowania [10, 11]. Równania zostały wyprowadzone w ramach trzech zaproponowanych modeli: modelu tolerancyjnego, modelu asymptotycznego oraz modelu asymptotyczno-tolerancyjnego.
Modelowanie płyt o funkcyjnej gradacji własności